An Ad-Hoc Crime Reporting Information Management System - Kommey, Benjamin; Opoku, Daniel; Asare-Appiah, Albert; Wiredu, George Ofori; Baah, Paul Kwasi (Universitas Komputer Indonesia, 2023)
Criminals often escape punishment due to delayed sharing of information with law enforcement agencies. The traditional method of reporting crimes is slow, thus, the need for a faster and modern approach, one that uses modern technology to apprehend perpetrators. It is therefore important to have a well-organized system for reporting criminal activities. This system should be free and easily accessible to the public. With information being delivered promptly and remotely, there is no need for visits to police stations, which can be time-consuming and tedious. This project aims to curb criminal activities by developing a smartphone application that enables victims or witnesses to report real-time information to security agencies, including GPS coordinates. The use of real-time data would prompt quick responses in emergency situations and make reactions proactive rather than reactive. The proposed methodology for the project involves designing and developing a user-friendly mobile app as well as a professional web application for security agencies. The creation of an integration platform allows for the registration of police stations and staff members. Feedback from users would help maintain and improve upon the app. Ultimately, this project aims at increasing public safety and improving crime reporting and management in Ghana by using modern technologies. By enabling citizens to report crimes in real-time, the mobile application has the potential to revolutionize crime reporting and foster a safer and secure environment. By collaborating with law enforcement agencies, the proposed solution can help provide a more efficient and proactive crime reporting system in Ghana.